Comparison of NOSE Scores Following Functional Septorhinoplasty Using Autologous versus Cadaveric Rib - Justicz, Natalie; Fuller, Jennifer C.; Levesque, Patricia; Lindsay, Robin W. (Facial Plastic Surgery, 2019)
In functional septorhinoplasty (FSRP), alternative grafting material is used if septal cartilage is insufficient for reconstructive needs. Autologous costal cartilage (ACC) and irradiated homologous costal cartilage (IHCC) are compared via the Nasal Obstruction Symptom Evaluation (NOSE) scale. One-hundred forty-one patients who underwent FSRP with ACC or IHCC between January 2013 and March 2018 were administered the NOSE scale pre- and postoperatively at 2, 4, 6, and 12 months. There was no significant difference in mean NOSE scores between the ACC and IHCC cohorts at the preoperative visit (68.5 [standard deviation, SD 24.1] and 71.7 [20.1], respectively; p < 0.6) or first postoperative visit (30.4 [26.6] and 33.9 [30.4], respectively; p < 0.6) or subsequent visits. NOSE scores demonstrated a clinically and statistically significant improvement at all follow-up time points for both the ACC and IHCC groups. Patients who underwent grafting with IHCC were significantly older than those with ACC; average age of 55.6 [SD: 17.3] versus 40.1 [SD:12.1]; (p < 0.001). Two IHCC (0.05%) patients had postoperative infections; both resolved with antibiotics, but one required revision surgery. Both ACC and IHCC provide reliable grafting material when septal cartilage is insufficient. In FSRP for nasal airway obstruction, ACC and IHCC both provide a clinically and statistically significant reduction in NOSE scores postoperatively that remain stable between follow-up time points. The authors find no difference in NOSE scores between the ACC and IHCC groups; however, IHCC did have a higher rate of postoperative infection. Both materials should be discussed with patients and are an important part of the informed consent process.
Keywords: rhinoplasty; cadaveric rib; autologous costal cartilage; irradiated homologous costal cartilage